Writing Proficiency in Narrative Texts Among Filipino 9 Students for the Development of E-SIPAT - TUBURAN, ARGIE (International Journal of Arts, Sciences and Education, 2025)
Writing proficiency is a fundamental skill for academic success, particularly in narrative composition, where students must demonstrate both creativity and coherence in writing stories. This study aimed to assess the narrative writing proficiency of Grade 9 students in Filipino and develop E-SIPAT, an instructional tool designed to enhance their writing skills. The researcher sought to identify common challenges students encounter in narrative writing, including organization, grammar, coherence, and creativity. The study employed a descriptive-developmental research design and aimed to determine and analyze the proficiency level in narrative writing among Grade 9 students. Based on the findings, the researcher developed a valid E-SIPAT as an instructional tool. Writing samples were collected from selected Grade 9 students and analyzed using a rubric assessing key aspects of narrative writing. The findings revealed that while students exhibited creativity, they struggled with coherence, grammar, and structural organization. These results underscored the need for a more structured and engaging instructional approach, which E-SIPAT aims to provide. The study concluded that targeted interventions, such as E-SIPAT, can enhance students’ narrative writing proficiency by offering guided exercises, feedback mechanisms, and interactive learning opportunities. This research can contribute to the improvement of writing instruction in secondary education. By addressing gaps in narrative writing skills, E-SIPAT has the potential to enhance students’ overall communication abilities, preparing them for academic and professional success.